Peran Guru BK Dalam Meningkatkan Perkembangan Kognitif Anak Usia Pertengahan - Fauziah Nasution; Yola Noperiyanti; Riska Aziza; Destya Aulia; Siti Hajar (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Jean Piaget, a Swiss scientist who lived from 1896 to 1980, created the cognitive development theory. His theory contributes many of the fundamental ideas in developmental psychology and has an impact on how the idea of intelligence is developed. According to Piaget, intelligence is the capacity to represent the world more precisely and apply logical operations to conceptual representations that are grounded in reality. This theory explores how schemata emerge and are acquired. Schema of a person's environment perception during developmental stages, when a person learns new ways to mentally represent information. Constructivism is the category this idea falls within. Keywords: Intelligence; Cognitive Development.